2014
DOI: 10.1016/j.bbagen.2014.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Cold-inducible RNA-binding protein mediates neuroinflammation in cerebral ischemia

Abstract: Background Neuroinflammation is a key cascade after cerebral ischemia. Excessive production of proinflammatory mediators in ischemia exacerbates brain injury. Cold-inducible RNA- binding protein (CIRP) is a newly discovered proinflammatory mediator that can be released into the circulation during hemorrhage or septic shock. Here, we examine the involvement of CIRP in brain injury during ischemic stroke. Methods Stroke was induced by middle cerebral artery occlusion (MCAO). In vitro hypoxia was conducted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
86
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 39 publications
11
86
1
Order By: Relevance
“…17, 18 We have demonstrated that Cirp −/− mice exhibit less tubular epithelial injury after RIR on histology corresponding to lower levels of serum injury markers BUN and creatinine. This is consistent with previous studies in which Cirp −/− mice show less organ injury after hemorrhage 12 and reduced brain infarct size after ischemic stroke 19 compared to WT mice.…”
Section: Discussionsupporting
confidence: 93%
“…17, 18 We have demonstrated that Cirp −/− mice exhibit less tubular epithelial injury after RIR on histology corresponding to lower levels of serum injury markers BUN and creatinine. This is consistent with previous studies in which Cirp −/− mice show less organ injury after hemorrhage 12 and reduced brain infarct size after ischemic stroke 19 compared to WT mice.…”
Section: Discussionsupporting
confidence: 93%
“…CIRP has been found to be constitutively expressed in low amounts in various tissues and its expression is up regulated during cellular stress (11, 12, 27). The human CIRP gene has been mapped to chromosome locus 19p13.3 and is 95.3% identical to the amino-acid sequence to that of mouse CIRP (10).…”
Section: Discussionmentioning
confidence: 99%
“…CIRBP is a novel damage associated molecular pattern (DAMP) that induces inflammation in mice (Qiang et al, 2013). Ischemic brain injury is reduced in CIRBP KOs (Zhou et al, 2014). In contrast, RBM3 appears to be a potent neuroprotective protein.…”
Section: Introductionmentioning
confidence: 99%